Treatable Traits in COPD - A Proposed Approach - Cardoso, João (2021)
The well-recognized individual heterogeneity within COPD patients has led to a growing interest in greater personalization in the approach of these patients. Thus, the treatable traits strategy has been proposed as a further step towards precision medicine in the management of chronic airway disease, both in stable phase and acute exacerbations. The aim of this paper is to perform a critical review on the treatable traits strategy and propose a guide to approach COPD patients in the light of this new concept. An innovative stepwise approach is proposed - a multidisciplinary model based on two distinct phases, with the potential to be implemented in both primary care and hospital settings. The first phase is the initial and focused assessment of a selected subset of treatable traits, which should be addressed in all COPD patients in both settings (primary care and hospital). As some patients may present with advanced disease at diagnosis or may progress despite this initial treatment requiring a more specialized assessment, they should progress to a second phase, in which a broader approach is recommended. Beyond stable COPD, we explore how the treatable traits strategy may be applied to reduce the risk of future exacerbations and improve the management of COPD exacerbations. Since many treatable traits have already been related to exacerbation risk, the strategy proposed here represents an opportunity to be proactive. Although it still lacks prospective validation, we believe this is the way forward for the future of the COPD approach.